Influence of Bridgman solidification on microstructures and magnetic behaviors of a non-equiatomic FeCoNiAlSi high-entropy alloy. (December 2015) - Zuo, Tingting; Yang, Xiao; Liaw, Peter K.; Zhang, Yong
Abstract: The non-equiatomic FeCoNiAlSi alloy is prepared by the Bridgman solidification (BS) technique at different withdrawal velocities (V = 30, 100, and 200 μm/s). Various characterization techniques have been used to study the microstructure and crystal orientation. The morphological evolutions accompanying the crystal growth of the alloy prepared at different withdrawal velocities are nearly the same, from equiaxed grains to columnar crystals. The transition of coercivity is closely related to the local microstructure, while the saturation magnetization changes little at different sites. The coercivity can be significantly reduced from the equiaxed grain area to the columnar crystal area when the applied magnetic field direction is parallel to the crystal growth direction, no matter what is the withdrawal velocity. In addition, the alloy possesses magnetic anisotropy when the applied magnetic field is in different directions. Highlights: Use the Bridgman solidification to fabricate the FeCoNiAl0.2 Si0.2 high-entropy alloy. The coarse column-like grains can be obtained by directional solidification. The coercivity of this FeCoNiAl0.2 Si0.2 alloy is largely reduced after directional solidification. After directional solidification, the FeCoNiAl0.2 Si0.2 alloy possesses magnetic anisotropy.